Early Tumor Shrinkage and Depth of Response Evaluation in Metastatic Pancreatic Cancer Treated with First Line Chemotherapy: An Observational Retrospective Cohort Study - Vivaldi, Caterina (Cancers (Basel), 2019)
Early tumor shrinkage (ETS) and depth of response (DoR) predict favorable outcomes in metastatic colorectal cancer. We aim to evaluate their prognostic role in metastatic pancreatic cancer (PC) patients treated with first-line modified-FOLFIRINOX (FOLFOXIRI) or Gemcitabine + Nab-paclitaxel (GemNab). Hence, 138 patients were tested for ETS, defined as a ≥20% reduction in the sum of target lesions’ longest diameters (SLD) after 6–8 weeks from baseline, and DoR, i.e., the maximum percentage shrinkage in the SLD from baseline. Association of ETS and DoR with progression-free survival (PFS) and overall survival (OS) was assessed. ETS was reached in 49 patients (39.5% in the FOLFOXIRI, 29.8% in the GemNab group; p = 0.280). In the overall population, ETS was significantly associated with better PFS (8.0 vs. 4.8 months, p < 0.001) and OS (13.2 vs. 9.7 months, p = 0.001). Median DoR was −27.5% (−29.4% with FOLFOXIRI and −21.4% with GemNab, p = 0.016): DoR was significantly associated with better PFS (9.0 vs. 6.7 months, p < 0.001) and OS (14.3 vs. 11.1 months, p = 0.031). Multivariate analysis confirmed both ETS and DoR are independently associated with PFS and OS. In conclusion, our study added evidence on the role of ETS and DoR in the prediction of outcome of PC patients treated with first-line combination chemotherapy.